Differences in Students’ Self-Efficacy and Learning Outcomes between Case-Based Learning and Direct Instruction in Basic Chemistry - Muliaman, Agus; Dewi, Ucia Mahya; Harahap, Lenni Khotimah; Ridho, Dimas (Journal of The Indonesian Society of Integrated Chemistry, 2025)
This study is motivated by low levels of self-efficacy and learning achievement among students in General Chemistry, which are often associated with the material's abstract nature and the limited use of active learning approaches. This study aims to examine differences in students’ self-efficacy and learning outcomes between the Case-Based Learning (CBL) model and the Direct Instruction (DI) model. The study employed an intact-group comparison (quasi-experimental) design involving 44 students from the Chemistry Education Program at Malikussaleh University, divided into an experimental group (CBL) and a control group (DI). Research instruments included a self-efficacy questionnaire and a multiple-choice posttest. The results revealed statistically significant differences between the two groups in both self-efficacy (t = 13.715; p < .001) and learning outcomes (t = 8.793; p < .001). Students in the CBL group obtained higher mean scores in self-efficacy (72.86) and learning outcomes (83.27) compared to those in the DI group. These findings indicate that Case-Based Learning is associated with higher self-efficacy and better learning outcomes in General Chemistry. The study suggests that CBL can be considered an alternative instructional approach to support active and contextual learning in science education.